2021
DOI: 10.3390/biomedicines9121782
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Improves Stemness of Human Adipose-Derived Stem Cells by Downmodulation of Mechanistic Target of Rapamycin (mTOR) and Extracellular Signal-Regulated Kinase (ERK) Signaling

Abstract: Adipose tissue plays an important role in regulating metabolic homeostasis by storing excess fat and protecting other organs from lipotoxicity. Aging is associated with central fat redistribution, culminating in a decrease in insulin-sensitive subcutaneous and an increase in insulin-resistant visceral adipose depots. Adipose-derived stem cells (ASCs) play an important role in the regeneration of adipose tissue. Aged ASCs show decreased stemness and regenerative potential due to the accumulation of oxidative st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…However, our findings of the maintained immunomodulatory features of dASCs agree with the results of a previous study on age-matched diabetic and nondiabetic donors. 41 It has been reported that metformin, a diabetic drug, improves the stemness, 84 and immunomodulatory potential, 85 of nondiabetic ASCs. The diabetic donors in the present study were administered different therapeutic regimens for T2D and the unknown effect(s) of medications on ASC functions could be a study limitation that needs to be taken into account in the future.…”
Section: Discussionmentioning
confidence: 99%
“…However, our findings of the maintained immunomodulatory features of dASCs agree with the results of a previous study on age-matched diabetic and nondiabetic donors. 41 It has been reported that metformin, a diabetic drug, improves the stemness, 84 and immunomodulatory potential, 85 of nondiabetic ASCs. The diabetic donors in the present study were administered different therapeutic regimens for T2D and the unknown effect(s) of medications on ASC functions could be a study limitation that needs to be taken into account in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Adipose tissue, particularly adipose-derived stem cells (ASCs), have been implicated as a significant contributor to inflammation during the aging process [ 21 , 32 ]. Hyperactivity of mitochondria is linked to detrimental ROS levels, inflammation, and reduced adipogenesis [ 21 , 33 ]. In this study, we analyzed the ROS levels in freshly isolated ASCs ex vivo among our young and aged mice cohorts.…”
Section: Resultsmentioning
confidence: 99%
“…Increased mitochondrial activity and ROS productions lead to the loss of quiescence, stemness, and increased differentiation of ASCs [ 21 , 33 , 34 ]. We compared the mitochondrial activity by measuring the mitochondrial membrane potential (TMRM staining) of freshly isolated CD34 + ASCs ex vivo in the subcutaneous and visceral adipose depots of young and aged mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies reveal that aging and obesity are closely related to the loss of stemness properties in adipose stem cells. Chinnapaka et al showed that metformin improved the stemness of human adipose-derived stem cells by downregulating the mTOR and ERK signaling 85 . Age-related adipose tissue dysfunction caused by stress-induced senescence of adipose stromal cells was ameliorated by metformin treatment 86 .…”
Section: Clinical Applicationsmentioning
confidence: 99%